2005
DOI: 10.1073/pnas.0505749102
|View full text |Cite
|
Sign up to set email alerts
|

Targeted down-regulation of cytochrome P450 enzymes for forage quality improvement in alfalfa ( Medicago sativa L.)

Abstract: Improving the digestibility of forages provides a means to enhance animal performance and protect the environment against excessive animal waste. Increased lignin content during maturity, and corresponding changes in lignin composition, correlate with decreased digestibility of forages. These relationships have yet to be investigated in isogenic systems. By targeting three specific cytochrome P450 enzymes of the lignin pathway for antisense downregulation, we generated transgenic alfalfa lines with a range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
328
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 316 publications
(361 citation statements)
references
References 52 publications
27
328
1
2
Order By: Relevance
“…No shift in S/G ratio can be inferred. These observation confirm previously reported observations by Bjurhager et al (2010) in the studied aspen genotype, Sewalt et al (1997) in tobacco, and Reddy et al (2005) in alfalfa. This further emphasizes the key role played by this enzyme in lignin biosynthesis.…”
Section: Morphological Effects Of Cinnamate 4-hydroxylase Down-regulasupporting
confidence: 93%
“…No shift in S/G ratio can be inferred. These observation confirm previously reported observations by Bjurhager et al (2010) in the studied aspen genotype, Sewalt et al (1997) in tobacco, and Reddy et al (2005) in alfalfa. This further emphasizes the key role played by this enzyme in lignin biosynthesis.…”
Section: Morphological Effects Of Cinnamate 4-hydroxylase Down-regulasupporting
confidence: 93%
“…Primer pairs for plant genotyping were as follows: left primer, 5′-GTGTCGTAGAGGCTTTGCTTG-3′; right primer, 5′-TTGTGGAAA-TATTTCCGGTTG-3′; and LBb1.3, 5′-ATTTTGCCGATTTCGGAAC-3′. Alfalfa antisense lines analyzed were as described previously (5,34,35). For the specific lines used, see SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…For example in transgenic maize have been reported that overexpression of GH11 (xynB) gene lead to enhances biomass enzymatic digestibility [93], while in poplar have showed that GH10 (xyn10A) gene by RANi silencing increasing biomass yield [94].…”
Section: Hemicellulose Biosynthesis and Degradationmentioning
confidence: 99%